Increasing the Tire Life Span by Means of Water Cooling - ABDULLAH, Mohd Azman; tamaldin, noreffendy; Abdul Aziz, Muhammad Khatib; Munawar, Ahmad Fadhli; Ngadiman, Mad Nasir (2013)
The life of tires depends on the frequency of usage, tire pressure level, weather and friction level between tire and road surface. Heat and friction will increase the wear and tear of the tire during long distance travel. Consequently, the life of the tire is reduced. In order to reduce the heat on the surface of the moving tire, a tire cooling system with water jet spray is designed and tested. The amount of heat dissipated from the tire is determined based on the reduction of the tire surface temperature after the water is spayed on the tire. With the immediate availability of the system components, the purpose of reducing the tire surface heat is achieved thus increase the tire life span.